2009
DOI: 10.1186/1471-2393-9-53
|View full text |Cite
|
Sign up to set email alerts
|

Surprisingly low compliance to local guidelines for risk factor based screening for gestational diabetes mellitus - A population-based study

Abstract: BackgroundScreening for gestational diabetes mellitus (GDM) is routine during pregnancy in many countries in the world. The screening programs are either based on general screening offered to all pregnant women or risk factor based screening stipulated in local clinical guidelines. The aims of this study were to investigate: 1) the compliance with local guidelines of screening for GDM and 2) the outcomes of pregnancy and birth in relation to risk factors of GDM and whether or not exposed to oral glucose tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 33 publications
3
36
0
5
Order By: Relevance
“…This study supports previous work which also showed poor compliance with local guidelines ranging from 31 to 61% appropriate risk based screening in Swedish and Thai cohorts respectively. (23,28) This study also is in keeping with an Irish national survey conducted at 19 units. Their aim was to assess implementation of local GDM screening guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…This study supports previous work which also showed poor compliance with local guidelines ranging from 31 to 61% appropriate risk based screening in Swedish and Thai cohorts respectively. (23,28) This study also is in keeping with an Irish national survey conducted at 19 units. Their aim was to assess implementation of local GDM screening guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well described that attendance for postnatal glucose tolerance testing is poor (Russell et al, 2006;Persson et al, 2009). Obese women should be informed that even in the presence of a negative postnatal GTT they are at increased risk of type 2 diabetes later in life and that weight loss can reduce this risk.…”
Section: Postpartum Carementioning
confidence: 99%
“…Oni su u populaciji komparabilnih trudnica u Švedskoj zabeležili prevalencu bolesti od 31.3% (Persson et al, 2009). Takođe, u saglasju je sa prevalencom šećerne bolesti trudnica u studiji Di Cianni-a i saradnika (Di Cianni et al, 2003).…”
Section: Epidemiologija I Karakteristike Studijske Populacijeunclassified
“…U populacionoj studiji preseka Persson i saradnika, koja je obuhvatila 822 trudnice podvrgnute skriningu GDM-a, 15.9% činile su žene koje su imale faktore rizika u aktuelnoj trudnoći (Persson et al, 2009). Od ovih faktora asimetrična akceleracija fetalnog rasta bila je najzastupljenija sa 59%, potom povećane vrednosti nasumično određivane glikemije sa 42%, dok je polihidramnion bio najmanje zastupljen sa 1% (Persson et al, 2009). Trudnice koje su razvile GDM rizične faktore tokom trudnoće bile su značajno većih vrednosti BMI u odnosu na trudnice bez faktora rizika u aktuelnoj trudnoći, 27.8 prema 24.3, p<0.001, što je slično našim rezultatima.…”
Section: Epidemiologija I Karakteristike Studijske Populacijeunclassified
See 1 more Smart Citation